2017
DOI: 10.14393/bj-v33n6a2017-37266
|View full text |Cite
|
Sign up to set email alerts
|

Industrial milk powder in bioassays for evaluation of cytotoxicity and genotoxicity

Abstract: Considering the widespread consumption of milk powder by the general population as well as the lack of studies on the toxicity of such industrialized foods, this study evaluated the cytotoxic and genotoxic potential of powdered milk from four reputed companies in the food market of Brazil and other South American countries. Milk samples were evaluated in root meristem cells of Allium cepa L., at concentrations of 0.065 and 0.13 g/mL, for 24 and 48 hours of exposure; and by means of cell viability in culture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Furthermore, data on analysis of ultra-pasteurized milk and milk containing products in the conditions of the Allium-test were published [26,27]. It was found that all analyzed samples had the significant anti-proliferative effect.…”
Section: The Main Partmentioning
confidence: 99%
“…Furthermore, data on analysis of ultra-pasteurized milk and milk containing products in the conditions of the Allium-test were published [26,27]. It was found that all analyzed samples had the significant anti-proliferative effect.…”
Section: The Main Partmentioning
confidence: 99%